Serpentine differentiation and polyploid evolution in Knautia arvensis agg. (Dipsacaceae). - Kolář, Filip (Jihočeská univerzita, 2009)
Evolutionary history of an intricate polyploid complex Knautia arvensis agg. in Central Europe has been studied using combined approach of molecular (AFLP, DNA-sequencing) and cytological (flow cytometry, karyology) techniques. Possible evolutionary scenario has been suggested for the whole complex and for the serpentine population in particular, based on critical assessment of results obtained from the different methods.
Serpentine differentiation and polyploid evolution in Knautia arvensis agg. (Dipsacaceae).